2014
DOI: 10.1503/cmaj.140289
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of quality improvement strategies for coordination of care to reduce use of health care services: a systematic review and meta-analysis

Abstract: Background: Frequent users of health care services are a relatively small group of patients who account for a disproportionately large amount of health care utilization. We conducted a metaanalysis of the effectiveness of interventions to improve the coordination of care to reduce health care utilization in this patient group. Methods:We searched MEDLINE, Embase and the Cochrane Library from inception until May 2014 for randomized clinical trials (RCTs) assessing quality improvement strategies for the coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
105
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 73 publications
1
105
0
4
Order By: Relevance
“…Strategies for care coordination examined in recent systematic reviews and meta-analyses of randomized controlled trials also found that involving more individuals in postdischarge care delivery (e.g., multidisciplinary teams and care managers) as well as supporting patient capacity for self-care led to significant reductions in hospital admissions or readmissions. 25,55 A compilation of studies also found that postdischarge follow-up was associated with reductions in readmission rates, [56][57][58][59][60][61] including one study conducted by our research team that highlighted particularly important reductions if follow-up was provided in a timely manner in a primary care setting (unpublished data). Consistent with our results, the evidence on team-based primary care models in Canada have pointed to small improvements in health utilization measures (not specifically in the postdischarge period), mainly lower rates of hospital admission and emergency department visits among older or chronically ill patients, and some improvements in processes of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies for care coordination examined in recent systematic reviews and meta-analyses of randomized controlled trials also found that involving more individuals in postdischarge care delivery (e.g., multidisciplinary teams and care managers) as well as supporting patient capacity for self-care led to significant reductions in hospital admissions or readmissions. 25,55 A compilation of studies also found that postdischarge follow-up was associated with reductions in readmission rates, [56][57][58][59][60][61] including one study conducted by our research team that highlighted particularly important reductions if follow-up was provided in a timely manner in a primary care setting (unpublished data). Consistent with our results, the evidence on team-based primary care models in Canada have pointed to small improvements in health utilization measures (not specifically in the postdischarge period), mainly lower rates of hospital admission and emergency department visits among older or chronically ill patients, and some improvements in processes of care.…”
Section: Discussionmentioning
confidence: 99%
“…25 Most interventions studied have been resource intensive and implemented in local settings. 26 Investigations of the capacity of innovations in primary care delivery implemented on a large scale to affect postdischarge outcomes are lacking.…”
mentioning
confidence: 99%
“…They found a 20% reduction in the risk of hos pital admissions after implementation of interventions involving case management protocols, team changes, promotion of patient selfmanagement or patient education. 2 When stratified by type of patient (those with mental illness v. those with chronic medical conditions other than mental illness; age ≄ 65 v. < 65 yr), significant reductions in hospital admissions persisted only among patients with chronic medical conditions other than mental illness. In additional subgroup analyses, a significant reduction in the proportion of patients visiting emergency departments was observed only among patients 65 years and older.…”
mentioning
confidence: 98%
“…2 For their meta-analysis, the authors obtained data for 7494 frequent users of health care services included in 36 randomized clinical trials of strategies to reduce emergency department visits, admissions to hospital or outpatient clinic visits. They found a 20% reduction in the risk of hos pital admissions after implementation of interventions involving case management protocols, team changes, promotion of patient selfmanagement or patient education.…”
mentioning
confidence: 99%
“…23,25,26 Improving upon patient discharge processes, providing better patient and/or caregiver education and promotion of selfmanagement, as well as enhanced transitioning support and coordination of care as the patient moves from the hospital to the home, are recommended approaches to reduce preventable readmissions. 27,28 In order to address the recognised problem of readmissions, the Hospitals Contribution Fund of Australia (HCF), Australia's largest for-purpose (not-for-profit) health insurer, instituted an intervention to provide post-discharge support for members admitted to hospital. The intervention is part of the broader My Health Guardian (MHG) program, a chronic disease management program initiated in 2009 as a long-term strategy to improve the health and well-being of covered members.…”
mentioning
confidence: 99%